A emergência do adolescente em conflito com a lei - Tauhata, Thiago Brandão Vieira (2020)
This work seeks, through genealogical research, the emergency of the adolescent in conflict with the law, constituted by a critical reflection that allows an analysis of antagonisms involved on the execution of socio-educational measures inside the governmental plan. Starting from an analysis of the legal documents of the 19th century, going through the emergency of the minor as objects of law in the 20th century, in association with the hygienists and eugenicist knowledge of the abnormal child until contemporary times, we observe with the promulgation of the Statute of the Child and Adolescent the emergency of a character resulting from biopolitics technics to be governed according to neoliberal governmentality. This character is created over time according to these techniques that are linked to the concept of socio-education. An inaccurate concept, undefined, but through the analysis of texts elaborated by the pedagogue Antonio Carlos Gomes da Costa, responsible for the inclusion of the term in the Statute and strong influencer in socio- educational works, allowed us to observe the elements for the birth of adolescents in conflict with a law according to neoliberal entrepreneurship racionality. This rationality coordinates itself with the socio-educational practice, limiting the accountability to adolescents, often excluding a diverse range of chronic historical and social factors present in its constitution. This implies increasing absence of State responsibility at the same time that a much broader government over the adolescent in conflict with a law according to a calculation of their freedom and life.